An energy self-sustaining scheduling scheme for UAV delivery networks - XU Jia; YUAN Ming; WU Sixu; TAN Xin; LUO Jian (物联网学报)
In recent years, the demand of express industry has increased rapidly, and the express industry is under increasing pressure. The unmanned aerial vehicle (UAV) delivery has become an effective supplement to vehicle delivery due to its low human cost, flexibility and convenience. However, UAVs are often limited by factors such as endurance and load capacity, requiring a low-cost and energy self-sustaining scheduling scheme for delivery and charging to support collaborative delivery of multiple UAVs. A two-stage self-sustaining multiple UAV cooperative delivery and charging scheduling scheme was proposed. The first stage aims at finding the delivery routes of UAVs to complete all delivery tasks in the region such that the number of UAVs was minimized under the energy and load capacity constraints of UAVs. The UAV delivery scheduling algorithm (UDSA) was proposed, and the approximation of UDSA was proved theoretically. The second stage aims to schedule the charging of UAVs with different arrival times to minimize the maximum charging completion time of all UAVs. An approximate UAV delivery scheduling algorithm (UCSA) was proposed to solve the problem. The simulation results show that, compared with the benchmark algorithm, UDSA can reduce the number of UAVs by 44.17% at most, and UCSA can reduce the maximum charging completion time by 18.87% at most.